2012
DOI: 10.3109/03009742.2012.676065
|View full text |Cite
|
Sign up to set email alerts
|

Functional disability and health-related quality of life in South Africans with early rheumatoid arthritis

Abstract: Background: The severity and predictors of functional disability and health-related quality of life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
4
27
0
Order By: Relevance
“…In patients with RA, aggravation of pain or symptoms of illness or a limitation in physical function has been reported to be closely associated with lowering HRQoL [9,10]. Studies of other chronic diseases have reported that a variety of demographic characteristics, including sex, body mass index (BMI), severity of illness, and age, will affect HRQoL [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with RA, aggravation of pain or symptoms of illness or a limitation in physical function has been reported to be closely associated with lowering HRQoL [9,10]. Studies of other chronic diseases have reported that a variety of demographic characteristics, including sex, body mass index (BMI), severity of illness, and age, will affect HRQoL [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Malemba et al found continued radiographic progression in Congo despite methotrexate, which was often given in low doses, and need for an additional DMARD; lack of follow-up was also a major issue [8]. Both Hodkinson et al from South Africa and Ibn Yacoub et al from Morocco found that RA significantly affects physical and mental aspects of patient's health-related quality of life (HRQoL), with even early RA having a broad impact on HRQoL in indigent South Africans [9,10]. Patients in South Africa showed substantial functional disability and suboptimal mental health despite 12 months of DMARD therapy, while in Morocco those taking methotrexate showed improvements in mental health and those taking biologics showed improvements in physical and social domains [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Both Hodkinson et al from South Africa and Ibn Yacoub et al from Morocco found that RA significantly affects physical and mental aspects of patient's health-related quality of life (HRQoL), with even early RA having a broad impact on HRQoL in indigent South Africans [9,10]. Patients in South Africa showed substantial functional disability and suboptimal mental health despite 12 months of DMARD therapy, while in Morocco those taking methotrexate showed improvements in mental health and those taking biologics showed improvements in physical and social domains [9,10]. The South African group also found that those who have an inadequate response to traditional DMARDs at 6 months are unlikely to show further improvement on these agents at 12 months, underscoring the need for better disease management through tight control, patient education and biologic therapy [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 46-year-old businesswoman in the Netherlands with RA is likely to have early intervention with disease-modifying antirheumatic drugs (DMARDs), resulting in disease remission or low disease activity within 6 months of symptom development [1]. In stark contrast, a 46-year-old domestic worker in peri-urban Soweto, South Africa, will probably experience late diagnosis of her RA and a delay in initiation of DMARD therapy often running into years [2]. Consequently, the South African patient is much more prone than her Dutch counterpart to develop significant functional disability and to be unemployed within 2 years of symptom onset.…”
mentioning
confidence: 99%